Apriori sample size estimation and reporting in original articles published from 2012 to 2020 in two Asian orthodontic journals - Shivangi Ramteke; Sekar Santhosh Kumar; Balasubramanian Madhan (Wolters Kluwer Medknow Publications, 2022)
AIMS: To evaluate the proportion and completeness of reporting apriori sample size estimation (SSE) in research articles published in the Journal of Orthodontic Science (JOS) and the Journal of Indian Orthodontic Society (JIOS). MATERIALS AND METHODS: All online research articles published in both journals from 2012 to 2020 were screened. Those reporting apriori SSE were analyzed for the study design and completeness of SSE reporting (outcome parameter and assumptions, Type I error, Power/type II error, one or two-tailed test, the method used, justifications for assumptions, adjustments in sample size, and the target sample size). Chi-square or Fisher exact test was used to analyze the differences between the journals in the proportions of articles reporting these characteristics. RESULTS: Twenty articles (13.2%) in JOS and 24 (8.3%) in JIOS, have reported apriori SSE [χ2 (1, N = 440) = 2.573, P=0.10]. Non-clinical and quasi-experimental studies formed nearly two-thirds of articles reporting SSE in JOS. Quasi-experimental (34%), randomized controlled trials (28%), and cross-sectional studies (24%) formed the bulk of articles reporting SSE in JIOS. Type II error/power was the most frequently reported characteristic in both (75% and 95.8% in JOS and JIOS, respectively), and the number of tails was the least (5% and 0%, respectively). More articles in JOS than JIOS reported the outcome variable used [65% vs. 12.5%, χ2 (1, N = 44) = 12.99, P<.001] and provided justifications for the assumptions [70% vs 33.3%, χ2 (1, N = 44) = 5.86, P = 0.01]. CONCLUSION: The extent and completeness of reporting apriori SSE are suboptimal in these journals and require prompt and stringent curative measures.